Research Infrastructures in the Humanities: the Challenge of ‘Visibility’ and ‘Impact’ - Žic Fuchs, Milena (2013)
RIs in the Humanities, just like in other domains of science, are being assessed and may be assessed even to a greater extent in the future. In this context of future developments, it can be expected that the “visibility” and the “impact” of an RI, its “usefulness” in the sense of showcasing research results, will become a factor in assessment processes. With the advent of Digital Humanities in the broadest sense of the word, the research landscape is showing elements of change. Research infrastructures, both those we find at “national levels”, as well as the big Pan-European ones, such as CLARIN and DARIAH, are becoming more and more known within different research communities within the Humanities themselves, but also further afield. In these developing contexts it is especially important to show how big Pan-European RIs “impact” concrete research. However, a number of questions arise pertaining to how “visible” these research infrastructures are to the huge community of scholars in the Humanities, as well as how do they foster concrete research and provide the basis for concrete research results. Or in other words, a question that may come up is: how will future assessments of research infrastructures in the Humanities evaluate the usefulness and productivity of the RI in question? Will RIs be assessed only on the basis of the number of users, or will the big Pan-European ones be able to showcase their “impact” in how they transcend national level databases of different kinds? Namely, the label Pan-European will have to be validated especially through scholarly outputs that show that national level RIs simply do not in some cases provide sufficient bases for “solving” particular research questions. This kind of argumentation will also help clarify the query, one sometimes hears in RI environments, as to whether Pan-European RIs in the Humanities are simply agglomerations or collections of national databases, or do they truly present and provide the basis for achieving added value in research.